A snare retrieval experience of coil migration in a large coronary artery fistula - Mithat Selvi; Hasan Gungor; Sevil Gulasti (International Journal of the Cardiovascular Academy, 2018)
A 45-year-old female patient was referred due to the abnormal myocardial perfusion scintigraphy showing ischemia in the inferior and lateral wall. Coronary arteries were normal, and a large fistula was detected from the proximal portion of the circumflex coronary artery (Cx) draining into the pulmonary artery. Percutaneous closure of the coronary artery fistula (CAF) was considered, and a 3 mm × 50 mm-Balt coil was planned to place the proximal portion of the fistulized artery. Unfortunately, during placement of the coil, it was opened early and migrated to the proximal segment of the Cx, the left anterior descending artery, and the distal part of the left main coronary artery. A snare was moved into the extra backup guiding catheter immediately. The migrated coil was retrieved with the snare successfully. Subsequently, 4 mm × 12 mm and 2 mm × 25 mm-Balt coils were placed in the mid portion of the fistulized artery until total occlusion was obtained. A CAF is described as a direct connection between one or more of the coronary arteries and a cardiac chamber or great vessel. The fistula may cause serious hemodynamic disturbances such as myocardial ischemia, high-flow heart failure, right ventricle volume overload, endocarditis, rupture, thrombosis, embolism, and arrhythmias. Percutaneous closure is the prior technique, in the absence of complex conditions such as multiple fistulas and large fistula branches and in cases where the fistula can be simply reached. There have been very rare data which contain complications about the percutaneous closure of CAFs.